Loci vexati nel De PLatone di Apuleio (190, 194, 206, 219, 229, 230, 241, 247, 252) - Giuseppina Magnaldi (Exemplaria Classica, 2014)
The study of the text transmitted for De Platone by Apuleius makes it possible to propose a new constitutio textus for some loci vexati: Plat. 190, 194, 206, 219, 229, 230, 241, 247, 252.